Sr-Nd-Hf Isotopic Disequilibrium During the Partial Melting of Metasediments: Insight From Himalayan Leucosome - Yang, Lei; Wang, Jia-Min; Liu, Xiao-Chi; Khanal, Gautam P.; Wu, Fu-Yuan (Frontiers in Earth Science, 2022)
Radiogenic isotopes of granitoids are widely applied to fingerprint the source of granitoids and study the magma mingling and assimilation processes, aiming to decipher the planetary differentiation. This weapon is based on the assumption that crustal melts inherit the radiogenic isotopes of protoliths. However, complicated melting processes in the crust would drive the radiogenic isotopes of melt away from the source, thus calling for a clear understanding of the behaviors of radiogenic isotopes during crustal melting. This study investigated the joint behavior of Rb-Sr, Sm-Nd, and Lu-Hf isotope systems during the melting of metasediments. Leucosome, schist and leucogranite samples were collected from the Nyalam, South Tibet, where the leucosome was produced by muscovite dehydration melting of metapelites. Results show that the leucosome has a broad range of Sr-Nd-Hf isotopes (87Sr/86Sri: 0.763248 – 0.875321, εNd(t): -14.6 – -11.6, εHf(t): -15.0 – -4.4), that deviate from the metasediments. We attributed it to the non-modal or disequilibrium melting of metapelites. The variation of Sr isotopes of leucosome formed due to preferential entry into the melt of muscovite relative to plagioclase during melting. The changing 87Sr/86Sri and 87Rb/86Sr of leucosome define an errorchron at ~ 500 Ma indicating an early Paleozoic tectono-thermal event supported by the U-Pb age of zircon cores (~460 Ma) in the leucosome. The Nd isotopes of leucosome are mainly controlled by the preferential dissolution of apatite relative to monazite. The inadequate dissolution of zircon caused more depleted initial Hf isotopes compositions in the leucosome than the source. However, the leucosome with a higher crystallization temperature has radiogenic isotopic composition closer to the source. It indicates that the melting temperature greatly affects the isotope equilibrium between source and melt.